2000
DOI: 10.1006/cbir.2000.0566
|View full text |Cite
|
Sign up to set email alerts
|

MULTIPLE RESPIRATORY BURSTS AS A RESPONSE TO VERATRATE STRESS IN RHODOCOCCUS ERYTHROPOLIS CELLS

Abstract: Although Rhodococcus spp. strains are able to degrade methoxyphenols by enzymatic means, the contact with veratric acid (3, 4-dimethoxybenzoic acid, hereafter called veratrate) is very stressful for the cells of Rhodococcus erythropolis DSM 1069 (Rh). Within 5 min of contact veratrate in phosphate buffer, the emergence of many vacuoles was observed in the cell body and respiratory bursts, with violent endogenous oxygen uptake, took place several times during the 24 h incubation. During these peaks (where the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Cells of Rhodococcus erythropolis (previously Nocardia sp DSM 1069) were cultivated on a liquid medium according to [17]. Cultures were grown in 250 ml conical flasks filled with 100 ml medium on a rotary shaker at 30°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells of Rhodococcus erythropolis (previously Nocardia sp DSM 1069) were cultivated on a liquid medium according to [17]. Cultures were grown in 250 ml conical flasks filled with 100 ml medium on a rotary shaker at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…In 1998, in a study of transformations of methoxyphenols in fungi and ligninolytic bacteria [16], we described the cyclic process of demethylation/methylation of veratric acid and vanillic acids in Rh. erythropolis [17], coupled with the activity of membrane bound NADH oxidase [18] and periodic reconstruction of the pool of veratric acid as a result of alternate activation of methylase and demethylase activities in these bacteria combined with changes in the levels of oxygen uptake. Figure 1 shows a hypothetical mechanism for these processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found (Malarczyk, 1989;Malarczyk & Kochmanska-Rdest, 1990;Malarczyk & Pazdzioch-Czochra, 2000) that the bacterium Rhodococcus erythropolis can utilize veratric acid as a carbon source. The bacterium was grown on agar medium supplemented with 0.04% guaiacol and stored on 2% agar slants according to Malarczyk (1984).…”
Section: Analogy Between Methoxyphenol Metabolism In Rhodococcus Erytmentioning
confidence: 99%
“…Almost identical optical densities of the bacterial suspension before and after incubation suggested that bacteria suspended in a bu!er with 0.02% veratric acid grew very slowly. Instead, oscillations in the concentrations of veratric acid and its demethylation products with the period of 8}10 hr have been observed (Malarczyk, 1989;Malarczyk & Kochmanska}Rdest, 1990;Malarczyk & Pazdzioch} Czochra, 1990, 2000. Two demethylation steps transformed veratric acid into protocatechuic acid.…”
Section: Analogy Between Methoxyphenol Metabolism In Rhodococcus Erytmentioning
confidence: 99%